The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/mice.12733
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian smoothing for input‐state estimation of structural systems

Abstract: Instantaneous output‐only inversion of a system with delayed appearance of input influences on the measured outputs via filtering methods suffer from intensive amplification of the observation noise in the estimated quantities due to the ill‐conditionedness. To remedy this issue, in this paper, a new unbiased recursive Bayesian smoothing method is developed for input‐state estimation of linear systems without direct feedthrough to reduce estimation uncertainty through an extended observation equation. By minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…From equation (35), it is found that any value of K k+1 is acceptable for the unbiased condition once 􏽢 Z k|k+N−1 is unbiased, i.e., (E[􏽢 e Z k ] � 0).…”
Section: Structural Control and Health Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…From equation (35), it is found that any value of K k+1 is acceptable for the unbiased condition once 􏽢 Z k|k+N−1 is unbiased, i.e., (E[􏽢 e Z k ] � 0).…”
Section: Structural Control and Health Monitoringmentioning
confidence: 99%
“…Tis addition improves the quality of the estimation at the current step since the addition is from the later steps. Actually, such a technique is the so-called smoothing that has been adopted by researchers [28,[31][32][33][34][35]. Recently, Ebrahimzadeh et al [35] proposed a method for joint identifcation of structural state and unknown inputs by combining smoothing technique, but structural parameters need to be known prior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, a modal identification framework based on a novel mode decomposition technique that identifies modal response and mode shape by the Kalman filter defined in modal space is proposed in this study. In general, Kalman filtering has been mainly applied to estimate the state variable using the measured response and further extended to reconstruct the external load using the inverse problem (e.g., Gillijns & De Moor, 2007;Gordon et al, 1993;Hassanabadi et al, 2022). Peng et al (2019), Hwang et al (2009), Kalman (1960), Kang et al (2012), Lei et al (2019), andNiu et al (2015) proposed a modal-based Kalman filter in conjunction with the optimum sensor placement method for the response reconstruction and excitation estimation of structures by using noisy acceleration and strain measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, a modal identification framework based on a novel mode decomposition technique that identifies modal response and mode shape by the Kalman filter defined in modal space is proposed in this study. In general, Kalman filtering has been mainly applied to estimate the state variable using the measured response and further extended to reconstruct the external load using the inverse problem (e.g., Gillijns & De Moor, 2007; Gordon et al., 1993; Hassanabadi et al., 2022). Peng et al.…”
Section: Introductionmentioning
confidence: 99%